Facial Nerve Anomaly in a Patient With a Parotid Tumor: A Case Report. Issue 18 (May 2016) - Lee, Dong Hoon; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract : Abstract: The branching pattern of the facial nerve varies among individuals. These variations increase the risk of facial nerve injury during parotid surgery. We report a new variation of the facial nerve and an unusual relationship with the retromandibular vein during parotid surgery. Clinicians should recognize this facial anomaly and the unusual relationship with the retromandibular vein to avoid injuring the facial nerve during parotid surgery.